2011
DOI: 10.1097/ico.0b013e3182282100
|View full text |Cite
|
Sign up to set email alerts
|

A New Target for Staphylococcus aureus Associated With Keratitis

Abstract: Staphylococcus aureus is a leading cause of keratitis, with an increased number of isolates exhibiting antibiotic resistance. Therefore, we need to understand the present situation regarding drug-resistant S. aureus in the ocular site. It has been shown that 35% of S. aureus isolates from ocular sites are methicillin-resistant Staphylococcus aureus (MRSA). MRSA isolates from ocular sites have a high rate of multiple mutations and high levels of resistance against fluoroquinolones. Wall teichoic acids (WTAs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A high-affinity human monoclonal antibody to S. aureus α-toxin has been found to be effective at reducing corneal damage 204 and a new antibiotic, targocil, has had some preliminary success at inhibiting the severity of staphylococcal infections. 205 Several potential therapies have been identified in Pseudomonas infection, including lithium chloride 206 and a caspase-1 inhibitor that reduces the amount of IL-1β produced. 207 Factors that improve corneal inflammation include the apoptotic Fas pathway which regulates the production of proinflammatory cytokines 208 and a phospho-inositol-3-kinase (PI3K)/Akt pathway that activates a receptor known as triggering receptor expressed on myeloid cells 2 (TREM-2).…”
Section: Potential Targeted Molecular Therapiesmentioning
confidence: 99%
“…A high-affinity human monoclonal antibody to S. aureus α-toxin has been found to be effective at reducing corneal damage 204 and a new antibiotic, targocil, has had some preliminary success at inhibiting the severity of staphylococcal infections. 205 Several potential therapies have been identified in Pseudomonas infection, including lithium chloride 206 and a caspase-1 inhibitor that reduces the amount of IL-1β produced. 207 Factors that improve corneal inflammation include the apoptotic Fas pathway which regulates the production of proinflammatory cytokines 208 and a phospho-inositol-3-kinase (PI3K)/Akt pathway that activates a receptor known as triggering receptor expressed on myeloid cells 2 (TREM-2).…”
Section: Potential Targeted Molecular Therapiesmentioning
confidence: 99%
“…Methicillin‐resistant staphylococci are usually resistant to a large number of commonly used antibiotics (penicillins, cephalosporins, and fluoroquinolones); 16 however, some reports demonstrated that chloramphenicol is effective against MRSA infections 12,17–19 . In the present case also, keratitis associated with MRSA was resolved by topical and systemic treatment with chloramphenicol followed by vancomycin.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, new antimicrobials with an improved activity against emerging or resistant MRSA strains are of crucial importance. [17][18][19] This study provides the first reported evidence that LZD has the therapeutic potential for the treatment of keratitis caused by MRSA. We found that topical LZD was as effective in reducing CFUs as topical VA. Another interesting finding of the present study is that the epithelial toxicity of LZD was less than that of VA.…”
Section: Discussionmentioning
confidence: 91%